Changing trend in reported hepatitis B incidence among residents of mainland China, 2004 - 2017 - Wei JIANG; Xian-hua MAO; Zhen-qiu LIU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze the trend of reported incidence of hepatitis B (HB) in mainland China from 2004 to 2017 to provide evidences for developing strategies on HB prevention and control. MethodsFrom National Public Health Science Data Center, we extracted the data on HB incidence in 31 provincial-level administrative divisions (not including Chinese Taiwan, Hong Kong Special Administrative Region and Macao Special Administrative Region) reported from March 2004 through March 2017. The average annual percentage change (AAPC) in region-, gender- and age group-specific HB incidence were calculated to assess variation trend of HB incidence during the period. ResultsFrom 2004 to 2017, the average reported incidence (per 100 000 population) of HB for the 31 divisions were 70.50, 75.57, 84.82, 89.00, 88.52, 88.82, 79.46, 81.54, 80.68, 71.12, 69.05, 68.57, 68.74 and 72.61, with no significant variation in the reported incidence as a whole (AAPC = 0.2%, P > 0.05); while, the increased HB incidences were reported in 9 of the divisions, with the APPCs of 5.80% for Shanxi, 4.20% for Anhui, 1.50% for Jiangxi, 1.70% for Hubei, 11.30% for Hunan, 6.70% for Guangdong, 3.50% for Guangxi Zhuang Autonomous Region, 3.10% for Hainan, 14.50% for Tibet Autonomous Region, and 4.40% for Xinjiang Production and Construction Corps, respectively (all P < 0.05). The mean reported annual HB incidence (per 100 000 population) during the period was 97.03 for males and 57.38 for females and there was no significant variation in the incidence for both the males (AAPC = - 0.1%) and the females (AAPC = 0.5%) (both P > 0.05). The age group-specific HB incidences (per 100 000 population) were 12.78, 17.64, 80.21, 211.00, 181.62 and 163.11 for the population aged 0 - 4, 5 - 9, 10 - 19, 20 - 39, 40 - 59, and 60 years and above, respectively; the age group-specific HB incidence decreased for the groups less than 20 years (AAPC = - 7.7%, - 13.6%, and - 11.6% for groups of 0 - 4, 5 - 9, 10 - 19 years, all P < 0.001) but increased for the age groups 60 years old and above (AAPC = 5.0%, P < 0.001). ConclusionDuring 2004 - 2017 in mainland China, the reported incidence of hepatitis B was not significantly changed generally but the incidence showed an increasing trend in some regions and the residents aged 60 years and above is the key population for hepatitis B prevention.